The leadership skills handbook 90 essential skills you need to be a leader - Owen, Jo. (New York Kogan Page Ltd, 2017)
Winner of the CMI Management Book of the Year Awards in the 2012/2013 New Manager category, The Leadership Skills Handbook from best-selling author Jo Owen reveals the essential skills you need to be an effective leader. It shows you what works in practice, not in theory, in crucial areas such as people skills, career skills, mindset skills, organization skills, personal values and behaviours. Each skill is presented in a concise, easy to follow format, with an accompanying framework to help you deploy it in your own life. The skills are about the real challenges real leaders have to master, and as you observe and record real-life examples of skills in action, you will be developing your own unique formula for success in the context that matters to you. Based on research from over a thousand leaders throughout the world at all levels in the public, private and voluntary sectors, it identifies the practical skills to make you even more successful, and offers guidance on all key topics.
Revised edition of the author's The leadership skills handbook, 2014.
Keywords: Leadership--Handbooks, manuals, etc